Screening and follow-up of pregestational diabetes and gestational diabetes mellitus: A survey of primary care physicians in Belgium. Issue 6 (December 2020) - Vercammen, Eveline; Van Hoof, Lucas; Vercammen, Chris; Goderis, Geert; Benhalima, Katrien
Highlights: Consensus on the best screening and follow-up for gestational diabetes is lacking. Overall adherence to guidelines by primary care physicians is favourable. The prevalence of gestational diabetes mellitus is underestimated. Increased awareness on the long-term risk for women with a history of GDM is needed. Abstract: Aims: Consensus regarding the best screening and follow-up strategy for gestational diabetes mellitus (GDM) is lacking, resulting in heterogeneity in clinical practice. We aimed to evaluate screening and follow-up practices for pregestational type 2 diabetes (T2DM) and GDM in primary care in Belgium. Methods: We performed an online survey among primary care physicians (PCPs) in the northern part of Belgium, Flanders. Results: Responses were obtained from 379 PCPs. Approximately two thirds of participants estimated the prevalence of pregestational T2DM and GDM in Flanders at 5% and <10%, respectively. The risk of developing T2DM within 10 years after a history of GDM was estimated at <30% by nearly half of all participants. The majority of interviewed PCPs screen for pre-existing T2DM and GDM. For T2DM, fasting glycaemia was used by 92.2% whereas for GDM, 75.2% used the 50 g glucose challenge test (GCT). Fasting glycaemia was the preferred test for postpartum follow-up. Conclusions: While overall guideline adherence appears favourable, the prevalence of GDM is underestimated. Increased awareness on the long-term risk for women with a history of GDM is needed. The overall preference for the two-step strategy with GCT indicates that the 2019 Flemish guidelines on GDM screening are attainable in primary care.